Empowering sexual self-care in HPV-positive women: A randomized trial of health belief model–Based education - Sanaz Akhondzadeh; Zahra Behboodi Moghadam; Masoumeh Namazi; Shima Haghani; Akram Ghahghaei Nezamabadi (PLoS ONE, 2025)
Introduction The human papillomavirus (HPV) is the most common sexually transmitted infection worldwide. The present study aimed to examine the impact of an educational intervention based on the Health Belief Model (HBM) on sexual self-care among women of reproductive age infected with HPV. Method This study was a randomized controlled trial with two parallel groups. Seventy-two women with HPV were selected through simple random sampling from Arash and Imam Khomeini hospitals in Tehran, Iran, and were allocated to a control group (n = 35) and an intervention group (n = 37). Participants in the intervention group received Health Belief Model (HBM)-based sexual self-care education during four weekly sessions, each lasting 45–60 minutes. The sessions were conducted using lectures, group discussions, question-and-answer sessions, PowerPoint presentations, pamphlets, educational videos, and role-playing. Data were collected using a demographic and obstetric information questionnaire, the Sexual Self-Care Questionnaire, and the HBM Questionnaire at three stages: before the intervention, immediately after, and 8 weeks after the completion of the intervention. Data analysis was performed using independent t-tests, Fisher’s exact test, chi-square test, and repeated measures ANOVA, with SPSS version 26 software. Results Both groups participating in the study were homogeneous in terms of demographic and obstetric characteristics (p > 0.05). The mean total score of sexual self-care and all its dimensions did not show a statistically significant difference between the intervention and control groups before the intervention (p = 0.275). However, immediately after and 8 weeks after the completion of the intervention, a significant increase was observed in the intervention group (p < 0.001). Additionally, the implementation of the intervention in the intervention group led to a significant increase in the constructs of perceived sensitivity, perceived benefits, cues to action, and self-efficacy, as well as a significant decrease in perceived barriers, both immediately and 8 weeks after the completion of the intervention (p < 0.001). However, the construct of perceived severity regarding sexual self-care did not show a statistically significant difference between the two groups at any time point (p > 0.05). Conclusion Based on the results of the study, education based on the Health Belief Model has been effective in improving sexual self-care and enhancing the constructs of the model in women with human papillomavirus (HPV). Therefore, it is recommended that this theory be considered by healthcare providers and midwives when educating patients with human papillomavirus. Trial registration This study was registered in the Iranian Registry of Clinical Trials on 2024/01/01 (code: IRCT20231223060503N1) URL: https://irct.behdasht.gov.ir/trial/74692